Development of Pluralism Education in Indonesia: A Qualitative Study - Nurman; Yusriadi, Yusriadi; Hamim, Sufian (Journal of Ethnic and Cultural Studies, 2022)
This study examines Indonesia’s pluralistic education strategy using qualitative research methods, including interviews, observation, and document examination, to collect data. Pluralistic education theory is applied as a theoretical framework. The research sites are three elementary schools in Riau Province, Indonesia, where students from different cultures gather to study. According to the study’s findings, existing education policies provide the possibility for minority students to attend public schools. The Ministry of Education and Culture has allowed schools to make policies that reflect the cultural diversity of their students. The findings also show that the curriculum includes references to diverse cultures, that textbooks include lessons that encourage students to live in harmony with individuals from different cultures, and that many schools have created multilingual education programs. A closer examination of these practices reveals that what appears to be acceptance of cultural variation is part of pluralism. Multicultural materials that have been introduced into the autonomous curriculum have mainly been included. The curriculum maintains the established characteristics that identify Indonesian culture.